Pengaruh Brand Ambassador, Brand Image, dan Promosi di Media Instagram Terhadap Keputusan Pembelian Pada Beauty Produk Skincare Bening’s Di Kota Surabaya (Fakultas Ekonomi Universitas Kadiri, 2022)
This study aims to determine the effect of brand ambassadors, brand image, and promotion partially and simultaneously on consumer purchasing decisions on Bening's beauty skincare products in Surabaya. The effect that we want to know is the direct or indirect effect. This study used a sample of 100 respondents. Sampling using the accidental sampling method with the characteristics of a minimum age of 17 years and followers of the Instagram account @beningclinic_surabaya. The test tools used are data analysis test and hypothesis testing. From this research test, it can be concluded that partially the brand ambassador variable, promotion has a positive and significant effect, and brand image has a positive and insignificant effect on consumer purchasing decisions on Bening's beauty skincare products in Suarabaya City. And simultaneously the variables of brand ambassador, brand image, and promotion simultaneously have a positive and significant effect on consumer purchasing decisions on Bening's beauty skincare products in the city of Surabaya